Social media engagement: factor motivate audiences participation on Zafesha Facebook advertising post / Mohammad Arif Hanafi Sadan - Sadan, Mohammad Arif Hanafi (2018)
Social media begin to expand and it could be powerful marketing platform if business owner can utilize it. In order to utilize social media, marketeers have to know the key factor to bring it success. By using Facebook Ads (FB ads) platform can boost advertising for some products, more efficient than Television advertising. It is because Facebook have billions of active users. By using Facebook ads, it will much cost saving rather than other media, but if marketeers don't know how to tackle the bidding algorithm, it could be expensive. By adapting user and gratification theory, this study main purpose is to find out what is the most motivating factor that influences user to keep engaging with business Facebook advert. If we master that most influence factor, we can produce the most quality advertising. And then, with high quality content, we can tackle the problem of low rate of post engagement and also improve the Faebook ads campaign quality, indirectly reduce the cost of Facebook Ads. Low cost of advertising will lead to higher profit margin. This study was using quantitative method to analyze the data collected. The results were analyzed by using Statistical Packages for social Science (SPSS) version 22.0 to get the frequency, mean, and correlation & regression. Overall, the result shows that all of the variables have positive relationship with the dependent variables, but only two of them are significant for this study.